Struggling with christology: Apolinarius of Laodicea and st Gregory of Nyssa - Orton, Robin (Vox Patrum, 2018)
The argument in the 380s between Gregory and Apolinarius, as set out Gregory’s Antirrheticus adversus Apolinarium, can be seen as a significant step in the development of the Church’s Christological teaching. Apolinarius’s notion that the eternal Logos took the place of Jesus Christ’s human mind is designed to establish the unity of his person, by providing a basis for the ontic continuity between the Second Person of the Trinity and Christ in his two natures. Commendably, he wants to counter any suggestion of separation between the human and divine natures (“two Christs”), which he sees as inevitably leading to an “adoptionist” view of Christ as a “God-filled man”; that would put Christ on the same level as the Old Testament prophets and could not form the basis of an adequate soteriology. Gregory argues convincingly however that Apolinarius’s “enfleshed mind” Christology would mean that Jesus Christ was not fully human and could not therefore save humankind. But in the face of Apolinarius’s challenge he cannot give an adequate account of Christ’s unity during his earthly career. He remains open to Apolinarius’s charge of a “divisive” Christology by in effect postponing the complete unity until after Christ’s glorification, when his divinity overwhelmed his humanity and removed all his human characteristics, in the same way as the water of the sea overwhelms a drop of vinegar dropped into it. On this basis he has, anachronistically but not unreasonably, been accused of taking a Nestorian view of Christ before his glorification and a monophysite one after it. Both Apolinarius’s stress on the unity of Christ and Gregory’s on the notion that ‘what is not assumed is not healed’ (Nazianzen’s phrase) were essential elements in what emerged seventy years later in the Chalcedonian definition.